2010
DOI: 10.1021/am100389x
|View full text |Cite
|
Sign up to set email alerts
|

Single Droplet Break-up in Controlled Mixed Flows

Abstract: In this work, the break-up dynamics of a single, Newtonian droplet dispersed in an immiscible Newtonian matrix undergoing a controlled mixture of shear and extensional flow is investigated using a homemade eccentric cylinder device. Hereto, different representative supercritical flows with varying shear/elongation balance have been applied. The effect of viscosity ratio is explored using droplets with a viscosity ratio of 0.1 and 1.3, respectively. In all cases, break-up is observed to proceed through an "end-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The lower viscosity polymer will encapsulate the higher viscosity polymer at a low shear rate. [32][33][34] According to Fig. 1, as the h* of PMMA is lower than that of PVDF, the PMMA will encapsulate the PVDF.…”
Section: Resultsmentioning
confidence: 99%
“…The lower viscosity polymer will encapsulate the higher viscosity polymer at a low shear rate. [32][33][34] According to Fig. 1, as the h* of PMMA is lower than that of PVDF, the PMMA will encapsulate the PVDF.…”
Section: Resultsmentioning
confidence: 99%
“…Additional passes of the emulsion through the colloid mill allow the drop size to be further reduced. While drop breakage in simple shear or Couette flow has been well studied (Cristini et al, 2003;Zhao, 2007;Renardy et al, 2002;Grace, 1982;Boonen et al, 2010), drop breakage mechanisms in colloid mills are not well understood. Common practice is to assume simple or extensional shear flow, in which drops break due to capillary instability when the ratio of the viscous stress to the interfacial tension force crosses a critical value (Wieringa et al, 1996;King and Keswani, 1994;Almeida-Rivera and Bongers, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In studies of multicomponent polymer blends of more than two phases, papers dedicated to this subject have shown that the morphology resulting from the competition between drops collision under flow followed by coalescence/encapsulation or drop breakup depends mainly on the interfacial and rheological properties. , The final droplet size distribution, under mixing, results from the balance between the present phenomena . Recently, the effect of compatibilization on the deformation and breakup of drops in stepwise increasing shear flow has been investigated…”
Section: Introductionmentioning
confidence: 99%